ADDITION OF PHYTASE IN ARTIFICIAL FEED GIVEN TO GIANT GOURAMI FISH FRY (Osphronemus goramy): PENAMBAHAN FITASE DALAM PAKAN BUATAN YANG DIBERIKAN PADA BENIH IKAN GURAMI (Osphronemus goramy) - Nikhlani, Andi; Pagoray, Henny; Riang, Agus (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Efficient feed is very important to understand the quality and quantity of feed concerning fish growth, if the fish consumes feed with the proper nutritional requirements for the fish’s body needs. The amount of nutrients used by the fish’s body will be minimal. One of the common problems in the process of making artificial feed is the use of vegetable protein in suboptimal feed due to the presence of anti-nutritional factors called phytic acid, which can reduce the amount of nutrients such as protein and minerals, and will affect the growth of the organism. This study aims to analyze the transformation and efficiency of feed in giant gourami fish fry by adding phytase enzymes to artificial feed. The data collected were displayed in tables and bar charts and analyzed using descriptive methods. The findings of the study stated that the addition of 3 mg/kg phytase to the feed produced better results than the control and other phytase doses (1 g/kg feed and 2 g/kg feed) in terms of feed conversion (1.02), feed utilization efficiency (97.77%), increased in total length (7.22 cm), and increased in absolute weight of giant gourami fish fry (197.44 g). During the study, water quality was measured at a temperature of 27-28°C, pH 6-7.3, oxygen levels of 4.8-6.3 mg/L, and ammonia levels of 0.02-0.08 mg/L.